Legal policy on corruption eradication in the new criminal code and the new criminal procedure code: Implications for the existence of the corruption eradication commission - Abdul Kadir (Komisi Pemberantasan Korupsi, 2026)
The update of the Criminal Code (KUHP) and the Criminal Procedure Code (KUHAP) is part of Indonesia’s national legal reform that affects the anti-corruption system, particularly the authority of the Corruption Eradication Commission (KPK). This study aims to analyze the position of corruption offenses within the national criminal law system following the enactment of the new KUHP and KUHAP, as well as to examine their implications for the KPK’s authority. The research employs a normative legal method using statutory, conceptual, and legal policy approaches through the analysis of relevant legal norms and legislative policies. The findings indicate that corruption offenses remain classified as special crimes (lex specialis) and extraordinary crimes, with their regulation continuing to be governed by special legislation outside the KUHP. The KUHP functions as a general criminal law regulating legal principles, criminal liability, and sentencing systems, while the KUHAP provides a procedural framework that places greater emphasis on the protection of human rights and the principles of due process of law. The reform of the KUHAP also requires adjustments to the KPK’s authority within the framework of an integrated criminal justice system without eliminating the special character of anti-corruption enforcement. Therefore, harmonization between general criminal law and special criminal law is necessary to maintain effectiveness, accountability, and justice in combating corruption in Indonesia.